Peningkatan Kualitas Ekowisata Berbasis Teknologi di Desa Wisata Cibereum Untuk Kolaborasi dan Keberlanjutan Lingkungan - Apriani, Rani; Pamungkas Satya Putra; Rahmi Zubaedah; Candra Hayatul Iman (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
The technology-based ecotourism quality improvement program aims to improve the quality of ecotourism in Karawang Regency by integrating information technology into the Tourism Awareness Village Groups (Pokdarwis), utilizing digital media as a promotional tool. This community engagement program was initiated to address the challenges faced by micro, small, and medium enterprises (MSMEs) and tourism awareness groups (Pokdarwis) in Cibereum Village, Karawang. While having strong potential, the program's implementation method involves conducting training covering digital marketing materials, creative content creation, social media management, and the use of Android-based applications. The results of this activity indicate an increase in the capacity of Pokdarwis to independently manage and promote their ecotourism destinations. The use of technology not only opens new economic opportunities but also encourages the creativity and independence of Pokdarwis in developing the tourism potential of their villages. Thus, this program contributes to the creation of a more modern, integrated, and sustainable ecotourism in Karawang Regency. In agriculture, handicrafts, and ecotourism, local communities face challenges such as limited branding, weak digital literacy, and unstructured management of tourism activities. These obstacles hamper market expansion and reduce the competitiveness of MSMEs and local ecotourism. To address these issues, an integrative approach was implemented by combining MSME digitalization with strengthening community-based ecotourism. This program was implemented through several stages, including participatory problem identification, integrated solution design, capacity building, technology introduction, and evaluation. Activities included creating visual identities and digital promotional tools for MSMEs, digital literacy training for villagers, and mentoring Pokdarwis (tourism groups) in managing environmentally friendly tourism. Additionally, appropriate technologies such as maggot cultivation were introduced as a solution for managing organic waste and providing alternative animal feed.